Effect of cooling slope casting and partial remelting treatment on microstructure and mechanical properties of A319-xMg2Si In-Situ composites - Yadav D.K.; Chakrabarty I. (My University, 2025)
The present study is aimed at evaluating the effect of cooling slope casting and partial remelting on hypoeutectic A319- 8Mg2Si and hypereutectic A319- 16 Mg2Si in-situ composites on the microstructural evolution and mechanical and wear properties. The characteristics are compared with those of conventional gravity castings. The microstructural features have been characterized by optical and scanning electron microscopy and X-ray diffraction analysis. Mechanical properties viz. bulk hardness, tensile properties and dry sliding wear characteristics with change in applied normal loads have been evaluated. The fractographs and worn surfaces are examined under scanning electron microscope. From the experimental findings it is observed that, the cooling slope casting can effectively refine and globularize α-Al grains, primary and eutectic Mg2Si and promote non-dendritic structures. Partial remelting further globularizes the matrix structures but develops microporosities. Improved hardness, tensile strength and dry sliding wear properties are obtained in cooling slope castings and in combined cooling slope casting with partial remelting. The improved properties are attributed to refinement and globularization of microstructural constituents with non-dendritic structures. Positive effects of microstructural features overshadowed the negative effect of porosity to the improvement in properties. © 2020 Elsevier B.V.